A DEVELOPMENT OF KNOWLEDGE CONSTRUCTION PACKAGE BASED ON CONSTRUCTIVIST TO ENHANCE THE MATHEMATICS PROBLEM SOLVING ABILITY ON LOGARITHM FOR GRADE VII STUDENTS - (Pantong Moonboupha), พานทอง มูลบัวภา; (Arphat Tiaotakul), อาพัทธ์ เตียวตระกูล; (Angkana Onthanee), อังคณา อ่อนธานี (Journal of Education and Innovation, 2018)
The research purposes were: 1) to construct and identify the efficiency of knowledge construction package based on Constructivist on “Logarithm” for grade VII Students, the efficiency criteria of 75/75, and 2) to implement knowledge construction package based on Constructivist by 2.1) compare the mathematics problem solving ability before and after using learning on “Logarithm”. 2.2) compare achievement before and after using learning on “Logarithm”. There were two steps of research and development as follows. The first step was to construct and identify the efficiency of knowledge construction package based on constructivist. Four packages of 14 hours developing and evaluated for their suitability by three experts and then knowledge construction package were used with grade VII students to find the efficiency criteria of 75/75. The research instrument were the knowledge construction package based on Constructivist on “Logarithm” for grade VII students, evaluation forms related to the suitability of the knowledge construction package based on Constructivist. The second step, implementing knowledge construction package based on Constructivist. The sample group was 42 students in grade VII students, second semester, academic year 2015 in Khosai Thapklo Phittaya School. One Group Pretest – Posttest Design. The research instrument were the knowledge construction package based on Constructivist on “Logarithm” for grade VII students, measure the mathematic problem solving ability and measure efficiency learning was used to find mean, standard deviation, and t – test dependent. The results were as follows; 1. Knowledge construction package based on Constructivist to enhance the mathematics problem solving ability and achievement on “Logarithm” for grade VII students Was consist of 1) Problem situation 2) Leaning Resource 3) Scaffolding 4) Problem solving Collaboration 5) Coaching. The evaluation by three experts showed that these knowledge Constructivist package were suitable at the high level ( = 4.46, S.D. = 0.48) when using with the sample group, it found that Knowledge Constructivist package had the efficiency of the mathematics problem solving ability equal to 78.04/84.81 and the efficiency achievement learning on “Logarithm” equal to 78.49/84.00. 2. The mathematics problem solving ability after using the Knowledge construction package based on Constructivist developed was significantly higher than before learning at the level of 0.01. 3. Learning achievement in “Logarithm” after using the Knowledge construction package based on Constructivist developed was significantly higher than before learning at the level of 0.01.